On the penaeid shrimps of the genus Metapenaeus Wood-Mason in Wood-Mason & Alcock, 1891 (Crustacea, Decapoda, Penaeidae) of Taiwan - Hsu, Yen-Cheng; Chen, Chien-Lin; Chan, Tin-Yam (Zootaxa, 2022)
Seven speceis in the penaeid shrimp genus Metapenaeus Wood-Mason in Wood-Mason & Alcock, 1891 are reported from Taiwan. Metapenaeus elegans De Man, 1907 is formerly recorded in Taiwan for the first time. A neotype is selected for the subspecies M. joyneri formosus Lee & Yu, 1977 and this action synonymizes this subspecies with the nominotypical form. A key to the species of Metapenaeus in Taiwan is provided.